Venom proteome of the box jellyfish Chironex fleckeri. - Diane L Brinkman; Ammar Aziz; Alex Loukas; Jeremy Potriquet; Jamie Seymour; Jason Mulvenna (PLoS ONE, 2012)
The nematocyst is a complex intracellular structure unique to Cnidaria. When triggered to discharge, the nematocyst explosively releases a long spiny, tubule that delivers an often highly venomous mixture of components. The box jellyfish, Chironex fleckeri, produces exceptionally potent and rapid-acting venom and its stings to humans cause severe localized and systemic effects that are potentially life-threatening. In an effort to identify toxins that could be responsible for the serious health effects caused by C. fleckeri and related species, we used a proteomic approach to profile the protein components of C. fleckeri venom. Collectively, 61 proteins were identified, including toxins and proteins important for nematocyte development and nematocyst formation (nematogenesis). The most abundant toxins identified were isoforms of a taxonomically restricted family of potent cnidarian proteins. These toxins are associated with cytolytic, nociceptive, inflammatory, dermonecrotic and lethal properties and expansion of this important protein family goes some way to explaining the destructive and potentially fatal effects of C. fleckeri venom. Venom proteins and their post-translational modifications (PTMs) were further characterized using toxin-specific antibodies and phosphoprotein/glycoprotein-specific stains. Results indicated that glycosylation is a common PTM of the toxin family while a lack of cross-reactivity by toxin-specific antibodies infers there is significant divergence in structure and possibly function among family members. This study provides insight into the depth and diversity of protein toxins produced by harmful box jellyfish and represents the first description of a cubozoan jellyfish venom proteome.